Flavonoid from the Sao Pedro Petro of tubers of cassava (Manihot esculenta Crantz) - Mohamad Azlan Nafiah (Tanjong Malim, 2019)
Flavonoid from the Sao Pedro Petro of tubers of cassava (Manihot esculenta Crantz) by Mohamad Azlan Nafiah